Andrographolide effect on both Plasmodium falciparum infected and non infected RBCs membranes - Ibraheem, Zaid Osamah; Abd. Majid, Roslaini; Md Noor, Sabariah; Mohd Sidek, Hasidah; Al-Zihiry, Khalid Jameel Kadhim; Yam, Mun Fei; Basir, Rusliza (Elsevier, 2015)
Objective: To explore whether its antiplasmodium effect of andrographolide is attributed to its plausible effect on the plasma membrane of both Plasmodium falciparum infected and non-infected RBCs.